Sustainability discourse, place and the green building - Kerr, Thor (Curtin University, 2008)
The world's nations concede that sustainable development is an appropriate response to the threat of global ecological destruction caused by industrialization. The discourse of sustainable development, or 'sustainability', legitimizes attempts to rearrange society through reproduction of the threat that humanity will annihilate itself unless its practices are reformed.This paper provides an analysis of sustainability discourses in the building industry and the ecological modernist storyline of 'green building'. It describes the application of Maarten Hajer’s discourse analysis methods to representations by industry professionals and academics at a series of conferences on sustainable built environments held in Australia, Singapore and Vietnam. The research findings describe how policies are produced and legitimized through nationally-contextualised sustainability discourses; and the findings indicate constraints in the production of policies for mitigating global ecological threats from industrialization.